Desain Website untuk Mendukung Promosi Digital Desa Wisata Tajur Halang - Nadiza Lediwara; Daffa Mahdy Brata; Kadek Rolavito; Tazky Khumaira Tsany; Sembada Denrineksa Bimorogo; Aulia Khamas Heikmakhtiar; Adam Mardamsyah (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: The purpose of this study is to design a website that supports digital promotion and information dissemination for Tajur Halang Tourism Village so that tourism potential can be introduced more widely and information can be accessed easily by the public and potential tourists. Research Methodology: This study was conducted in Tajur Halang Village. The research used a User-Centered Design (UCD) approach which includes needs analysis, information architecture design, interface design, prototyping, and evaluation with village partners. Data were collected through observation, interviews, and discussions with village administrators. The website design and prototype were developed using website design tools and evaluated through user feedback. Results: The results of this study are a responsive website design that has a clear navigation structure, informative content about tourism potential, and a consistent visual appearance. The website prototype can present tourism information more systematically and make it easier for users to access village tourism information. Conclusions: The website design using the User-Centered Design approach can support digital promotion for Tajur Halang Tourism Village and improve the presentation of tourism information in a more structured and professional way. Limitations: This study is limited to the design and prototype stage, and the website has not yet been fully implemented and tested with a larger number of users. Contributions: This study contributes to the development of digital promotion strategies for tourism villages and can be used as a reference for other villages that want to develop tourism information systems or digital promotion media.